Challenges and Barriers Towards Medical Research Among Medicaland Dental Students of Public Sector Medical College - Omer, Umme Ammarah; Abbasi , Muhammad Ali; Razzaq, Ayan-ur-; Qureshi, Shaista Noor; Tiwana, Madeeha; Zahid , Khaula (Pakistan Armed Forces Medical Journal, 2024)
Objectives: This study aims to identify challenges and attitudes of undergraduate medical students during research engagement and propose strategies to overcome them.Study Design: The study is a cross-sectional study.  Place and Duration of Study: The study was conducted in the Medical and Dental departments of Army Medical College Rawalpindi. Duration of the research spanned from March 2023 to May 2023, following approval from the Ethical Review Committee of Army Medical College (ERC/ID/264 Dated: 03 March 2023).Patients and Methods: A 29-item questionnaire for the quantitative cross-sectional study was adopted from another study and was further validated by a panel of 06 experts in the field of medical education and research. A pilot test was conducted to verify the construct of the adopted tool. A random sampling technique was employed to select the participants. The inclusion criteria were undergraduate medical students who have studied medical research modules. Non-respondents and unwilling participants fall under the exclusion criteria of the study. Analysis was conducted using the Statistical Package for Social Sciences (SPSS) program, Version 26.Results: Out of a total of 135 participants, 94.1% belonged to MBBS and 5.9% were in the BDS training program. Female turnover was 59.3% and male participants were 40.7%. Common barriers reported by the participants were “lack of information” (28.1% strongly agree, 38.1% agreeConclusion: Despite barriers, a significant proportion of participants actively engaged in research, with high publication rates (81.5%) and recognition (76.3%). While the majority recognized the importance of medical research (88.1%),